Theoretical Basics of Internal Auditing at Public Administration Institutions - Ficzeréné Nagymihály, Kornélia; Csiszárik-Kocsir, Ágnes; Hágen, István Zsombor (Acta Agraria Debreceniensis, 2007)
In the past months, in the time of the reforms of the new millennium, the modernisation and transformation of the public sphere have been a constant issue in Hungary due to globalisation and the country’s accession to the European Union. The provision of transparency and comparability is required from each member state by the challenges of globalisation, legal harmonisation and the unification process. That is why it is essential to harmonise and adjust to one another the internal and external auditing systems of public institutions on the levels of both the institutions and sectors. The study reviews the theoretical foundations and basic principles of the public institutions’ internal auditing system, as well as it aims to provide an overall picture of the legal background of the auditing system and its changes. By including the main principles, standards and the most important regulations, the study’s informative approach aims to assist anyone interested in the further and deeper research into the subject.